To solve the system of equations:
- \( 8x - 4y = -28 \)
- \( 2x - 6y = 8 \)
We can use substitution or elimination. I will simplify the first equation and solve the system step by step.
Step 1: Simplify the equations if possible
Starting with the first equation:
\[ 8x - 4y = -28 \]
We can simplify it by dividing everything by 4:
\[ 2x - y = -7 \quad \text{(Equation 1)} \]
Now we look at the second equation:
\[ 2x - 6y = 8 \]
Step 2: Solve for one variable
From Equation 1, we express \(y\) in terms of \(x\):
\[ y = 2x + 7 \quad \text{(Substituting for y)} \]
Step 3: Substitute into the second equation
Now substitute \(y\) into the second equation:
\[ 2x - 6(2x + 7) = 8 \]
Distributing the -6:
\[ 2x - 12x - 42 = 8 \]
Combine like terms:
\[ -10x - 42 = 8 \]
Step 4: Solve for \(x\)
Add 42 to both sides:
\[ -10x = 50 \]
Divide by -10:
\[ x = -5 \]
Step 5: Find \(y\)
Substitute \(x = -5\) back into Equation 1 to get \(y\):
\[ y = 2(-5) + 7 \]
\[ y = -10 + 7 = -3 \]
Solution
The solution to the system of equations is:
\[ (x, y) = (-5, -3) \]
Thus, the answer is:
\[ \text{(−5,−3)} \]